The Impact of Dysmetabolic Sarcopenia Among Insulin Sensitive Tissues: A Narrative Review - Armandi, Angelo; Rosso, Chiara; Caviglia, Gian Paolo; Ribaldone, Davide Giuseppe; Bugianesi, Elisabetta (Frontiers in Endocrinology, 2021)
Sarcopenia is a common muscular affection among elderly individuals. More recently, it has been recognized as the skeletal muscle (SM) expression of the metabolic syndrome. The prevalence of sarcopenia is increasing along with visceral obesity, to which it is tightly associated. Nonetheless, it is a still underreported entity by clinicians, despite the worsening in disease burden and reduced patient quality of life. Recognition of sarcopenia is clinically challenging, and variability in study populations and diagnostic methods across the clinical studies makes it hard to reach a strong evidence. Impaired insulin activity in SM is responsible for the altered molecular pathways and clinical manifestations of sarcopenia, which is morphologically expressed by myosteatosis. Lipotoxicity, oxidative stress and adipose tissue-derived inflammation lead to both alterations in glucose disposal and protein synthesis in SM, with raising insulin resistance (IR) and SM atrophy. In particular, hyperleptinemia and leptin resistance interfere directly with SM activity, but also with the release of Growth Hormone from the hypohysis, leading to a lack in its anabolic effect on SM. Moreover, sarcopenia is independently associated to liver fibrosis in Non-Alcoholic Fatty Liver Disease (NAFLD), which in turn worsens SM functionality through the secretion of proinflammatory heptokines. The cross-talk between the liver and SM in the IR setting is of crucial relevance, given the high prevalence of NAFLD and the reciprocal impact of insulin-sensitive tissues on the overall disease burden. Along with the efforts of non-invasive diagnostic approaches, irisin and myostatin are two myokines currently evaluated as potential biomarkers for diagnosis and prognostication. Decreased irisin levels seem to be potentially associated to sarcopenia, whereas increased myostatin has shown to negatively impact on sarcopenia in pre-clinical studies. Gene variants in irisin have been explored with regard to the impact on the liver disease phenotype, with conflicting results. The gut-muscle axis has gain relevance with the evidence that insulin resistance-derived gut dysbiosis is responsible for increased endotoxemia and reduction in short-chain free fatty acids, directly affecting and predisposing to sarcopenia. Based on the current evidence, more efforts are needed to increase awareness and improve the management of sarcopenic patients.